THE FORTIFICATION OF REBON SHRIMP (Mysis relicta)PROTEIN ISOLATES TO THE PREMIX FLOUR OF EGG SNACK-HEAD FISH - br Bangun, Feby Frisca br Bangun Frisca; Suparmi, Suparmi; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The purpose of the research was to observe theeffect of the fortification of protein isolates of rebon shrimp to sneak-head eggpremix flour. The research was conducted at the Laboratory of Fish Processing Technology, the Laboratory of Fishery Chemistry and the Integrated Laboratory in the Fisheries and Marine Faculty at the Universitas Riau Pekanbaru in January - March 2019. The research used an experimental method by conducting the treatment of adding protein isolates of rebon shrimp at 4 levels (0%, 5%, 10%, and 15%) to the sneak-head eggpremix flour. The variables assessed were organoleptic quality (appearance, odor, texture andflavor) and the chemical analysis, including the content of water, ash, lipid, protein andcarbohydrate (by difference). The results showed that the fortification of rebon shrimp isolates protein at the concentration of 15% was the best treatment indicated by the highest organoleptic value. The product was characterized by clean, normal, bright with the appearance score at 8.0; tasty aroma of rebon shrimp and seasoning wafted with the odor score at 8,4; very smooth and dry texture scored at 8.0; very tasty with shrimp flavor mixed with specific taste of sneak-head egg with the flavor score at 8.5. The product was containing moisture, ash, lipid, protein and carbohydrate (by difference)at 3.97%, 1.31%, 8.56%, 39,32% and 46,83%, respectively. Keywords: Isolate protein,premix flour,rebon shrimp, sneak-head egg